Upgrade of Lesions Initially Diagnosed as Low-Grade Gastric Dysplasia upon Forceps Biopsy Following Endoscopic Resection (Gut and Liver, 2011)
Background/Aims Gastric dysplasia is generally accepted to be the precursor lesion of gastric carcinoma. Approximately 25% to 35% of histological diagnoses based on endoscopic forcep biopsies for gastric dysplastic lesions change following endoscopic resection (ER). The aim of this study was to determine the predictive endoscopic features of high-grade gastric dysplasia (HGD) or early gastric cancer (EGC) following ER for lesions initially diagnosed as low-grade dysplasia (LGD) by a forceps biopsy. Methods : To determine predictive variables for upgraded histology (LGD to HGD or EGC). The lesion size, gross endoscopic appearance, location, and surface nodularity or redness as well as the presence of a depressed portion, Helicobacter pylori infection, and intestinal metaplasia were retrospectively investigated. Results : Among 251 LGDs diagnosed by an initial forceps biopsy, the diagnoses of 100 lesions (39.8%) changed following the ER; 56 of 251 LGDs (22.3%) were diagnosed as HGD, 39 (15.5%) as adenocarcinoma, and 5 (2.0%) as chronic gastritis. In a univariate analysis, large lesions (>15 mm), those with a depressed portion, and those with surface nodularity were significantly correlated with a upgraded histology classification following ER. In a multivariate analysis, a large size (>15 mm; odds ratio [OR], 2.8; 95% confidence interval [CI], 1.46 to 5.43) and a depressed portion in the lesion (OR, 2.7; 95% CI, 1.44 to 5.03) were predictive factors for upgraded histology following ER. Conclusion : s Our study shows that a substantial proportion of diagnoses of low-grade gastric dysplasias based on forceps biopsies were not representative of the entire lesion. We recommend ER for lesions with a depressed portion and for those larger than 15 mm.